Comparative study on the blood physiological, biochemical indexes and liver histology of Schizothorax wangchiachii (♀), Percocypris pingi (♂) and their hybrids - Jiange Huang; Dayou Zhuo; Mengyao Wang; Saiqin Yeerda; Jiajun Huang; Xiaofeng Qin; Minfang Lu; Zhijian Wang; Xiaohong Liu (Frontiers in Marine Science, 2024)
Distant hybridization is a well-established technique in genetic breeding for cultivation of superior traits. Previous studies have shown that, hybrids derived from the cross between Schizothorax wangchiachii (♀) and Percocypris pingi (♂) are significantly different from their parents in terms of growth performance, feeding behavior and disease resistance. Both cellular and plasma components of blood are integral to immune system, and erythrocytes serve as the sole cells for transporting oxygen which makes energy available for the growth, development, immune responses and all other physiological activities. In order to understand ecological adaptive strategies and also the underlying physiological and biochemical mechanisms of fish with different characteristics, the present study used offsprings and hybrids produced by artificial reproduction of the same batch of domesticated S. wangchiachii , P. pingi broodstock as the experimental fish, and analyses of biochemical indexes, differential leucocytes counts and histological examination of liver sections were performed. Results showed that the proportions of lymphocytes and thrombocytes in P. pingi were significantly higher than those in S. wangchiachii (P<0.05), while the proportions of granulocytes and monocytes in S. wangchiachii were significantly higher than those in P. pingi (P<0.05). In contrast, all blood cell values of hybrids fell between those of its parent species, with the exception of the percentage of thrombocytes, which was the highest of the three. The erythrocyte area, perimeter and short diameter of hybrid fish were significantly higher than those of S. wangchiachii and P. pingi (P<0.0001), while P. pingi exhibited the smallest erythrocyte values. Hepatocyte area, perimeter and short diameter were also significantly higher in hybrids than in S. wangchiachii and P. pingi , and P. pingi had the smallest hepatocyte area, perimeter, long diameter and short diameter. However, size and perimeter of hepatic nucleus of hybrids were the smallest. The number of Kupffer cells per unit area of liver was significantly greater in S. wangchiachii than in hybrids and Percocypris pingi (P<0.05). In terms of biochemical markers, plasma C-reactive protein level was nearly undetectable in S. wangchiachii , but it could reach 10 mg/L in both P. pingi and hybrids. Besides, plasma total bile acids was significantly higher in S. wangchiachii than in P. pingi (P<0.01), and hybrids fell in intermediate level. These results suggest that there may be differences in the immune functions among S. wangchiachii , P. pingi , and their hybrids, as well as in their liver metabolism and protein synthesis capabilities. These findings here might provide some crucial clues in understanding the biodiversity and fish adaptation, further promote the development of wild fish cultivation.